RESPONSIBILITY OF THE BOARD OF DIRECTORS ON IMPLEMENTATION OF COMPANY WHEN CONFLICT WITH COMMISSIONERS - Indrasari Kresnadjaja; I Gusti Agung Jordi; I Putu Lingga Dhananjaya; I Made Pria Dharsana (Journal Equity of Law and Governance, 2021)
Limited Liability Company hereinafter referred to as Company is a legal entity which is a capital partnership. It is established based on an agreement to conduct a business activities with authorized capital. This is entirely divided into shares or individual legal entities which all meet the criteria for Micro and meet the requirements set out in The Law on Limited Liability Companies and its implementing regulations (Law Number 11 of 2020 regarding Job Creation) which changes several definitions of Limited Liability Companies as regulated in Law Number 40 of 2007 (hereinafter referred to as UUPT). The research method used in this writing is a normative legal research method which analyzes the problem through an approach to legislation, theory and applicable principles. Talking about the applicable provisions in the important organs of the Limited Liability Company. The Limited Liability Company Organ itself is a Group of Organs consisting of the General Meeting of Shareholders (hereinafter referred to as GMS), the Board of Directors, and the Board of Commissioners. Among the three organs of a limited liability company, the directors have full authority over the company. Based on the provisions of Article 1 paragraph (5) of the Company Law, â€œThe Board of Directors is an organ of the Company which is authorized and fully responsible for the management of the Company for the benefit of the Company in accordance with the aims and objectives of the Company and represents the Company both inside and outside the court in accordance with the provisions of the articles of associationâ€. Besides that, in a company, the board of directors is the party who has the most important role, both in managing the company, managing it, and advancing it. The Board of Directors is appointed by the GMS, as referred to in Article 94 paragraph (1) of the Company Law, that; â€œMembers of the Board of Directors are appointed by the GMS.â€ And further paragraph (3) members of the Board of Directors are appointed for a certain period of time and may be reappointed.